Combinatorial algorithms : 30th International Workshop, IWOCA 2019, Pisa, Italy, July 23-25, 2019, Proceedings /: 30th International Workshop, IWOCA 2019, Pisa, Italy, July 23-25, 2019, Proceedings. ([2019]) - Unknown
No abstract available